2021
DOI: 10.15294/jpfi.v17i1.26301
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Creativity and Attitudes Caring The Environment of Junior High School Students: Study of Environmental Physics Learning Using Learning Modules

Abstract: The natural and socio-cultural environment of the Wonosobo community has various potentials that can be explored and developed to support the science learning process. Pranotomongso is a form of culture used by farmers to cultivate nature. This study aims to determine the application of ethnoscience-based integrated science learning to foster environmental awareness and student creativity. This research is a quantitative study using the True Experimental method, with a Posttest Only Control Design, the samplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
1
1
0
1
Order By: Relevance
“…The e-Module in this research was developed specifically to facilitate students' scientific creativity and was integrated with Javanese cultural ethnoscience according to students' conditions. This is supported by previous research, namely that ethnoscience-based learning provides opportunities for students to develop their ideas and creativity (Amelia et al, 2021).…”
Section: Introductionsupporting
confidence: 66%
“…The e-Module in this research was developed specifically to facilitate students' scientific creativity and was integrated with Javanese cultural ethnoscience according to students' conditions. This is supported by previous research, namely that ethnoscience-based learning provides opportunities for students to develop their ideas and creativity (Amelia et al, 2021).…”
Section: Introductionsupporting
confidence: 66%
“…Penelitian ini difokusikan untuk melihat keefektifan modul dalam meningkatkan sikap peduli lingkungan mahasiswa (Amelia et al, 2021;Damayanti, 2023;Harahap & Tanjung, 2023;Indrayanti et al, 2021;Sari & Pujiastuti, 2023;Suwondo et al, 2019). Nilai keefektifan modul perubahan lingkungan berbasis ESQ didapatkan dari hasil pengisian angket sikap peduli ISSN: 2356-069X E-ISSN: 2715-4343 DOI: 10.33059/jj.10i2.8752 lingkungan oleh mahasiswa.…”
Section: Pembahasanunclassified
“…Student creativity needs to be trained during the learning process in class because it can stimulate students to think divergently so they can actively carry out beneficial activities, especially for the environment (Halek et al 2021;Cheng 2019). Various learning studies have been conducted to determine effective strategies for increasing student creativity (Amelia et al, 2021). However, it has yet to be found that it has been implemented in learning based on environmental education.…”
Section: Introductionmentioning
confidence: 99%